(untitled) (American Journal of Islam and Society, 2006)
Growing out of a course that the authors have taught jointly since 1996 at the International Islamic University Malaysia (“Creative Thinking and Problem Solving”), this book is designed for use as an undergraduate textbook on these issues from an Islamic viewpoint. Since Muslims generally deplore their own community’s lack of creativity and desperately need to reverse their technological and scientific dependence on other countries, the authors seek to present a realistic strategy to help them regain the innovative spirit that characterized classical Islamic civilization. Drawing on cognitive psychology and related disciplines in western academia, they begin with the assumption that creativity is a learned skill, rather than the personal endowment of an elite corps of humanity. The book then develops their second assumption: Islamic values and perspectives can be enriched through a dialogue with western social sciences. The first part is devoted to Islamic civilization’s contribution to human civilization: tafakkur and other Qur’anic words calling for people to think creatively (chapter 1); applying secular “thinking styles” literature to the Qur’an, including the inquisitive, objective, positive, hypothetical, rational, reflective/contemplative, visual, metaphorical, analogical, emotional, perceptual, conceptual, intuitive, scientific, and wishful thinking styles (chapter 2); analyzing the concept of ijtihad and its vocation to constantly adapt Islamic law to changing circumstances and find creative solutions to persistent socioeconomic and political challenges (chapter 3); and summarizing Muslim contributions to science, philosophy, and medicine (chapter 4) ...